MODEL PREDIKSI NILAI PERUSAHAAN MELALUI KEPEMILIKAN MANAJERIAL DAN SET KESEMPATAN INVESTASI - Herry Laksito; Sutapa Sutapa (Jurnal Keuangan dan Perbankan, 2011)
This study empirically examined the effect of managerial ownership on firm value of Investment OpportunitySet with mediation. Model, this research examined corporate governance measured by the shares of thecompanys value with the mediation set of investment opportunities. The purpose of this study was to analyzethe effect on the value of corporate governance mediation firm with an investment opportunity sets on manufacturingcompanies listed in Indonesia Stock Exchange. The populations in this study were all of manufacturingcompanies listed in Indonesia Stock Exchange and reporting financial statement in the Indonesian capitalmarket directory during the period 2005-2007. Determination of sample used purposive sampling. The datamet the characteristic of 37 firms. Statistical method used was path analysis. The results showed that managerialstock ownership (corporate governance) did not affect the value of a company with a negative direction.Managerial stock ownership (corporate governance) affected the investment opportunity set (IOS). IOS did notaffect the value of the company and investment opportunity set could not significantly mediate the effect ofmanagerial ownership (corporate governance) against the value of the firm.